Rational drug use awareness of the nurses in the Turkish Republic of Northern Cyprus Near East University Hospital [Kuzey Kıbrıs Türk Cumhuriyeti Yakın Doǧu Üniversitesi Hastanesi'ndeki hemşirelerin akılcı ilaç kullanımı konusundaki farkındalıǧı] - (:unkn) unknown (Marmara University, 2012)
OBJECTIVE: Irrational use of drugs cause a serious economical burden for many countries. Rational drug use RDU requires a teamwork of health providers. Prescribers, pharmacists and nurses have an important role in RDU. In this study, we aimed to evaluate the knowledge and attitude of the nurses about RDU. METHODS: The present study was conducted to evaluate the knowledge of the 44 nurses (who consented to participate in the study) in Turkish Republic of Northern Cyprus (T.R.N.C.) Near East University Hospital towards rational drug use. RESULTS: All the nurses were female with an average age of 38 ± 13. Half of them had high school degree, 11.4% associate degree and 38.6 bachelor degree. Average experience in nursing was 16 ± 12 years. Seventy seven percent of the nurses told that they did not know the RUD. The most common problems about order/prescription was claimed to be illegible order/prescription (76.7%), unavailability of the drug in the market/ hospital pharmacy stocks (37.5%), missing instructions (46.2%), dosing error (24.4%), inappropriate pharmaceutical form (8.8%). The nurses stated that they consulted physicians (97.8%) or their colleagues (89.2%) in case of a drug related problem. Also they stated that they generally informed patients about the time of drug administration (when to take the drug- before or after a meal), while they informed patients about drug/ nutrient interactions. Eighty percent told that they were satisfied by the way they practiced their profession and 96% said they would be willing to attend a training course about RDU. CONCLUSION: Our survey results demonstrated a need for educational program on RDU for nurses.
Keywords: Cyprus; Education; Nurse; Patient; Pharmacotherapy; Problems; Rational drug use